Interpretasi Konsep Laba dalam Laporan Keuangan terhadap Beban Pajak dan Keputusan Investasi pada Perusahaan Terdaftar di BEI - Aprillia, Dinda Dwi (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to analyze the impact of profit interpretation in financial statements on tax burden and investment decisions in companies listed on the Indonesia Stock Exchange (IDX). This research employs a descriptive qualitative approach using secondary data in the form of annual financial statements from three IDX-listed companies: PT Bank Central Asia Tbk (BBCA), PT Blue Bird Tbk (BIRD), and PT Hotel Sahid Jaya International Tbk (SHID) for the years 2023–2024. The key indicators analyzed include profit before tax, tax expense, net profit, earnings per share (EPS), dividends, and changes in equity. The results show that companies with positive profits, such as BBCA and BIRD, experienced a proportional increase in tax expenses and demonstrated significant equity growth, which influenced investor appeal. On the other hand, a company with losses like SHID was not subject to tax and experienced a decline in equity, making it less attractive to investors. The interpretation of profit in financial statements has a direct impact on tax obligations and investor perception. Therefore, transparency and accuracy in profit reporting are essential to support corporate sustainability and enhance market trust.